DAMPAK SUPLEMENTASI 1,25-DIHIDROKSIVITAMIN DJTERHADAP EKSKRESI KALSIUM URIN DAN AKUMULASI KALSIUM TULANG TIKUS WISTAR PANHISTEREKTOMI YANG MENGKONSUMSI TERI TAWAR - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The obyectives of the research were to study the impact of 1.25-dihydroxyvitamin DJ suplementation on urinary Ca excretion and Ca accumulation in panhisterectomized Wistarrats fed with unsalted anchovy. Fifteen female Wistar rats, 8 weeks of age, were divided into three groups (control, panhisterectomy, and panhisterectomy+ I,25-dihydroxyvitamin DJ supplement) of five each. At 19 weeks of age, they were placed into individual metabolic cages for a balance study.From day 4 to II ofthe balance study, every day,the feed left over, urine, and feces were collected and recorded for Ca analyses. The results ofthe research showed that Ca comsumption in panhisterectomized rats consuming I,25-dihydroxyvitamin DJsupplement are not significantly different from the panhisterectomized rats not consuming I,25-dihydroxyvitamin D)supplement. The fecal Ca excretion was significantly higher (P